False Gastric Diverticulum Arising from the Pylorus Associated with Gastric Outlet Obstruction - Umesh Jayarajah; Oshan Basnayake; Pradeep Wijerathne; Jayan Jayasinghe; Nilesh Fernandopulle; Ishan De Zoysa (Case Reports in Surgery)
A gastric diverticulum is an outpouching from the stomach wall. It is usually seen in the posterior gastric wall and the gastric antrum. Diverticula arising from the pyloric region are extremely rare. A 59-year-old female presented with progressively worsening symptoms of gastric outlet obstruction associated with dyspepsia and vague abdominal pain for 5 years. A large, thin-walled, wide-mouthed, false gastric diverticulum (filled with undigested food) arising from the pylorus associated with gastric outlet stenosis was found by endoscopy and CT imaging. Multiple biopsies from the region excluded a gastric malignancy. A gastrojejunostomy and jejunojejunostomy were performed to bypass the obstruction which successfully relieved the symptoms. This is an unusual site for gastric diverticula, and when associated with gastric outlet obstruction, further distention of the diverticulum may cause more obstruction with worsening symptoms.